2022
DOI: 10.1038/s41467-022-28833-4
|View full text |Cite
|
Sign up to set email alerts
|

Apoplastic class III peroxidases PRX62 and PRX69 promote Arabidopsis root hair growth at low temperature

Abstract: Root Hairs (RHs) growth is influenced by endogenous and by external environmental signals that coordinately regulate its final cell size. We have recently determined that RH growth was unexpectedly boosted when Arabidopsis thaliana seedlings are cultivated at low temperatures. It was proposed that RH growth plasticity in response to low temperature was linked to a reduced nutrient availability in the media. Here, we explore the molecular basis of this RH growth response by using a Genome Wide Association Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 95 publications
1
30
0
Order By: Relevance
“…For instance, Prx40 was found essential to proper anther and pollen development [ 56 ]. As for the Grip-exclusive upregulated genes under salt stress, Prx15 was involved in ROS-induced programmed cell death [ 57 ], while Prx62 was related to seed germination as it was expressed in the micropylar endosperm [ 5 ], and it was recently characterized to be also involved in regulating root hair elongation under cold conditions [ 58 ]. Moreover, Prx49 and Prx52, which were upregulated in Col-0 under salt stress, were involved in the abscisic acid early signaling in Arabidopsis [ 59 ] and in lignin biosynthesis and xylem development [ 60 ], respectively ( Figure 7 b).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Prx40 was found essential to proper anther and pollen development [ 56 ]. As for the Grip-exclusive upregulated genes under salt stress, Prx15 was involved in ROS-induced programmed cell death [ 57 ], while Prx62 was related to seed germination as it was expressed in the micropylar endosperm [ 5 ], and it was recently characterized to be also involved in regulating root hair elongation under cold conditions [ 58 ]. Moreover, Prx49 and Prx52, which were upregulated in Col-0 under salt stress, were involved in the abscisic acid early signaling in Arabidopsis [ 59 ] and in lignin biosynthesis and xylem development [ 60 ], respectively ( Figure 7 b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently identified new molecular components involved in low temperature RH growth. We found that cell wall-apoplastic related peroxidases, PRX62 and PRX69, are important for low temperature triggered RH growth by inducing changes in ROS homeostasis and cell wall EXTENSIN insolubilization 15 . Although relevant advances have been achieved in our understanding on how RH growth occurs at low temperature, it is still unclear how nutrient availability caused by low temperature is perceived in the RH cells and the extent of molecular responses that control RH growth.…”
Section: Introductionmentioning
confidence: 87%
“… 39 , 40 Thus, abnormal accumulation of ROS in root hair cells brings about exacerbated growth or root hair burst. 6 Respiratory burst homologs (RBOHs) and peroxidases (PRXs) are the main generators of ROS at the apoplast in plants. 41–44 The ROS primarily generated by RBOH oxidase are required for normal root hair elongation.…”
Section: Regulation Of Root Hair Elongation By Reactive Oxygen Specie...mentioning
confidence: 99%
“… 60 Moreover, PRX62 and PRX69 stimulate Arabidopsis root hair elongation at low temperatures, likely through modulating ROS homeostasis and cell wall extensin-insolubilization. 6 PRX01, PRX44, and PRX73 function in ROS homeostasis and control Tyr-crosslinking of cell wall extensins during polar expansion of root hair cells. 7 , 61 RSL4 directly binds to the promoter regions of RBOHC and PRX1, 44, 73 , and 69 to increase their expression, triggering apoplast oxidation and polarized root hair elongation.…”
Section: Regulation Of Root Hair Elongation By Reactive Oxygen Specie...mentioning
confidence: 99%
See 1 more Smart Citation